Effect of hormone replacement therapy on periodontal health in post-menopausal women in Jeddah, Saudi Arabia - Raneem Ageel; Bahaa Abaalkhail; Zuhair S. Natto (BMC Women's Health)
Abstract Background Menopause marks the cessation of menstrual cycles and brings significant changes to a woman’s body, including oral health alterations. While hormone replacement therapy (HRT) is commonly used to alleviate menopause symptoms, its impact on oral health, particularly periodontal conditions, has not been well studied in Saudi Arabia. Periodontitis, a disease that destroys the bone and soft tissue of the mouth, becomes more prevalent post-menopause. This study investigates the effect of HRT on periodontal health in post-menopausal women. Methodology A case-control study was conducted with 372 post-menopausal Saudi women from multiple healthcare facilities in Jeddah, Kingdom of Saudi Arabia. The study included 186 women with periodontitis (cases) and 186 women with healthy periodontium (controls). Periodontal health was assessed using the American Academy of Periodontology (AAP) 2017 classification and a validated questionnaire. Secondary objectives concerning periodontal parameters like Clinical attachment loss (CAL), saliva secretion rate, and bone loss were also measured in HRT users compared to non-users. Odds ratios (OR) and logistic regression were used for categorical data analysis, while t-tests and linear regression examined the relationship between numerical variables. Results HRT use was significantly associated with a lower prevalence of periodontitis. The odds of having periodontitis were 3.2 times lower in HRT users compared to non-users (OR = 0.31, p < 0.05, 95% CI: 0.11–0.89). After adjusting for medical and demographic variables, HRT users had approximately six times lower odds of having periodontitis (OR = 0.17, p < 0.05, 95% CI: 0.04–0.81). However, HRT use did not significantly impact the severity of periodontitis once the disease was present. When secondary outcomes were measured, HRT usage had a significant association with decreased clinical attachment loss (Coef = -1.13, p < 0.05, 95% CI: (-2.26, -0.02)); however, this significance was lost after adjusting for medical and social variables. HRT usage did not have a significant effect on bone loss and saliva level, which were measured both as categorical and numerical variables. Conclusion & recommendations HRT is associated with a lower prevalence of periodontitis but does not affect its severity. While collaborative care between dental and medical professionals is recommended, further research is needed to address study limitations and explore different HRT formulations and their impact on periodontal health.